2006
DOI: 10.1128/cvi.13.1.84-89.2006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Immunoglobulin G Antibodies toNeospora caninumin Humans: High Seropositivity Rates in Patients Who Are Infected by Human Immunodeficiency Virus or Have Neurological Disorders

Abstract: Considering that little is known about the epidemiology of Neospora caninum infection in humans, particularly in populations with high Toxoplasma gondii infection rates, the present study aimed to investigate the presence of antibodies to N. caninum in T. gondii-seropositive and -seronegative individuals. A total of 256 serum samples divided into four groups (61 samples from human immunodeficiency virus [HIV]-positive patients, 50 samples from patients with neurological disorders, 91 samples from newborns, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
1
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 28 publications
2
93
1
18
Order By: Relevance
“…The importance of N. caninum as a zoonotic agent remains unknown, but N. caninum antibodies have been detected in humans in the United States (TRANAS et al, 1999) and Brazil (LOBATO et al, 2006;BENETTI et al, 2009). In Brazil, IgG antibodies against N. caninum were detected in patients infected with human immunodeficiency virus (HIV) and in patients with neurological disorders, suggesting the possibility that neosporosis could be an opportunistic parasite in immunocompromised patients (LOBATO et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of N. caninum as a zoonotic agent remains unknown, but N. caninum antibodies have been detected in humans in the United States (TRANAS et al, 1999) and Brazil (LOBATO et al, 2006;BENETTI et al, 2009). In Brazil, IgG antibodies against N. caninum were detected in patients infected with human immunodeficiency virus (HIV) and in patients with neurological disorders, suggesting the possibility that neosporosis could be an opportunistic parasite in immunocompromised patients (LOBATO et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, IgG antibodies against N. caninum were detected in patients infected with human immunodeficiency virus (HIV) and in patients with neurological disorders, suggesting the possibility that neosporosis could be an opportunistic parasite in immunocompromised patients (LOBATO et al, 2006). Furthermore, the authors found a positive correlation between infections by N. caninum and T. gondii, and suggested that further studies are needed to evaluate N. caninum infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In MG, serum samples from HIV-infected patients (Group I), patients with neurological disorders (Group II), newborns (Group III) and a healthy control (Group IV) by IFAT (1:50) were assayed for N. caninum antibodies by indirect ELISA to detect immunoglobulin G (IgG), utilizing soluble antigen and IB as a confirmatory test, with lysed tachyzoites as antigen (LOBATO et al, 2006). They found IB positive patients in all groups, and HIV-infected patients and those with neurological disorders patients presented significantly higher prevalence.…”
Section: Clinical Infectionsmentioning
confidence: 99%
“…Para N. caninum, existem evidências sorológicas em seres humanos, no entanto, não foram descritos relatos comprovados da doença. Por outro lado, tal possibilidade não pode ser descartada (TRANAS et al, 1999;LOBATO et al, 2006).…”
Section: Introductionunclassified